2015
DOI: 10.1111/obr.12257
|View full text |Cite
|
Sign up to set email alerts
|

Appetite control and energy balance: impact of exercise

Abstract: 2Exercise is widely regarded as one of the most valuable components of behaviour that can influence body weight and therefore help in the prevention and management of obesity. Indeed long term controlled trials show a clear dose related effect of exercise on body weight. However, there is a suspicion, particularly fuelled by media reports, that exercise serves to increase hunger and drive up food intake thereby nullifying the energy expended through activity. Not everyone performing regular exercise will lose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
214
2
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(235 citation statements)
references
References 62 publications
5
214
2
14
Order By: Relevance
“…The effect of acute exercise on energy intake has been widely explored and discussed in adults for the last 20 years (3,5,6). Recently, the interest around this question in pediatric population emerged (10).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of acute exercise on energy intake has been widely explored and discussed in adults for the last 20 years (3,5,6). Recently, the interest around this question in pediatric population emerged (10).…”
Section: Discussionmentioning
confidence: 99%
“…Overvekt er rangert som den fjerde største risikofaktoren for den globale sykdomsbyrden (1), mens den i Norge har ligget på tredjeplass (2). Det er en viss enighet om kostens betydning for overvekt (3,4), mens betydningen av fysisk aktivitet derimot er mer omdiskutert (5,6).…”
Section: Fysisk Aktivitet Og Vektreduksjonunclassified
“…etter en treningsøkt, vil trolig høyere fysisk aktivitetsnivå på-virke appetittreguleringen ved at man blir raskere mett ved påfølgende måltid, grunnet økt følsomhet for sentrale hormoner som leptin og insulin. Det resulterer dermed ikke nødvendigvis i høyere energiinntak (5,6).…”
Section: Korttids-og Langtidseffektunclassified
See 1 more Smart Citation
“…In spite of the influence of purposeful exercise on appetite, appetite-related hormones and food intake, varying amounts of habitual physical activity may modify appetitive responses [18]. Evidence from cross-sectional research has indicated that inactive individuals have impaired energy intake regulation which may facilitate a positive energy balance and consequential weight gain [10,98]. This section will discuss recent research that has explored differences in appetite-related responses to exercise interventions between habitually active verses inactive individuals.…”
Section: Habitual Physical Activity and Exercisementioning
confidence: 99%